Targeting amphiregulin (AREG) derived from senescent stromal cells diminishes cancer resistance and averts programmed cell death 1 ligand (PD‐L1)‐mediated immunosuppression. Issue 6 (7th September 2019) - Xu, Qixia; Long, Qilai; Zhu, Dexiang; Fu, Da; Zhang, Boyi; Han, Liu; Qian, Min; Guo, Jianming; Xu, Jianmin; Cao, Liu; Chin, Y. Eugene; Coppé, Jean‐Philippe; et al.
Abstract: Aging is characterized by a progressive loss of physiological integrity, while cancer represents one of the primary pathological factors that severely threaten human lifespan and healthspan. In clinical oncology, drug resistance limits the efficacy of most anticancer treatments, and identification of major mechanisms remains a key to solve this challenging issue. Here, we highlight the multifaceted senescence‐associated secretory phenotype (SASP), which comprises numerous soluble factors including amphiregulin (AREG). Production of AREG is triggered by DNA damage to stromal cells, which passively enter senescence in the tumor microenvironment (TME), a process that remarkably enhances cancer malignancy including acquired resistance mediated by EGFR. Furthermore, paracrine AREG induces programmed cell death 1 ligand (PD‐L1) expression in recipient cancer cells and creates an immunosuppressive TME via immune checkpoint activation against cytotoxic lymphocytes. Targeting AREG not only minimized chemoresistance of cancer cells, but also restored immunocompetency when combined with classical chemotherapy in humanized animals. Our study underscores the potential of in vivo SASP in driving the TME‐mediated drug resistance and shaping an immunosuppressive niche, and provides the proof of principle of targeting major SASP factors to improve therapeutic outcome in cancer medicine, the success of which can substantially reduce aging‐related morbidity and mortality. Abstract : The senescence‐associated secretory phenotype (SASP) comprises numerous soluble factors including AREG. Intensively produced by treatment‐damaged stroma, AREG drives cancer‐acquired resistance and induces passive formation of an immunosuppressive niche. Experimentally detectable in the circulating blood, AREG is both a stroma‐derived SASP factor meriting therapeutic intervention and a novel noninvasive biomarker to predict adverse outcome of post‐treatment cancer patients in clinical medicine.